Between conflict and cooperation: The Contrasting image of the Ottoman Turks in Late Medieval Ragusan Sources - Filipović, Emir O. (De Medio Aevo, 2023)
The present study focuses on the late medieval commune of Dubrovnik, known in Latin and Italian sources as Ragusa, and its precarious relationship with the Ottoman Turks, while placing a particular emphasis on the various strategies that Ragusans employed throughout the fourteenth and fifteenth centuries in attempting to navigate a difficult political existence between their own interests and the interests of a unified Christendom which stood in complete opposition to the Ottomans. Numerous surviving records created in Ragusa at the time depict the Ottoman Turks in a completely inconsistent light, demonstrating that historians, as always, need to take particular care about accepting claims from diplomatic sources at face value, and that relations between Christians and Muslims during the Ottoman conquest of the Balkans were not always as unambiguous or constantly hostile as they are often presented to be in contemporary works, modern historiography and public discourse.
Keywords: Ragusa/Dubrovnik; Ottoman Turks; Ottoman Empire; Mediterranean; diplomacy